2017
DOI: 10.1021/acs.orglett.6b03671
|View full text |Cite
|
Sign up to set email alerts
|

Key Structural Elements for Cellular Uptake of Acinetobactin, a Major Siderophore of Acinetobacter baumannii

Abstract: Acinetobactin is a major siderophore utilized by the human pathogen Acinetobacter baumannii. The rapid acquisition of drug resistance by A. baumannii has garnered concern globally. Herein, acinetobactin and systematically generated analogues were prepared and characterized; the binding and cellular delivery of Fe(III) by the analogues were evaluated. This investigation not only led to the clarification of the physiologically relevant acinetobactin structure but also revealed several key structural elements for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 24 publications
2
29
1
Order By: Relevance
“…The nature of one of the main siderophore molecules taken up by A. baumannii is important, both for understanding the physiology of this significant pathogen and for the rational design of the so-called ‘trojan horse’ antibiotics. Conflicting reports are extant in the literature as to whether the molecule which is taken up is preacinetobactin or acinetobactin (Song et al, 2017; Shapiro and Wencewicz, 2017). As our own experiments have shown, small amounts of impurities that are hard to eliminate coupled to ready conversion of preacinetobactin to acinetobactin poses significant technical challenges in resolving this problem.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nature of one of the main siderophore molecules taken up by A. baumannii is important, both for understanding the physiology of this significant pathogen and for the rational design of the so-called ‘trojan horse’ antibiotics. Conflicting reports are extant in the literature as to whether the molecule which is taken up is preacinetobactin or acinetobactin (Song et al, 2017; Shapiro and Wencewicz, 2017). As our own experiments have shown, small amounts of impurities that are hard to eliminate coupled to ready conversion of preacinetobactin to acinetobactin poses significant technical challenges in resolving this problem.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, one of the oxygens and a carbon of catechol seem plausible candidates for expansion (Figure 4b). Shapiro and Wencewicz (2017) and Song et al (2017) reported important indications about the role of the different portions of both ligands by comparing the biological activity of multiple derivatives and checking complex formation through UV-vis spectroscopy. These studies confirm the 2-OH of preacinetobactin is essential but changes at the 3 and 5 positions of the catechol are well tolerated (no information on the four position was reported).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…baumannii . Importantly, the essential features required for iron coordination by, and cellular uptake of acinetobactin have been identified, along with a promising sites for the conjugation of an antibiotic [ 38 , 44 , 91 ]. Interestingly, in assessing the development of resistance to another experimental sideromycin (BAL30072), A .…”
Section: Discussionmentioning
confidence: 99%
“…Other virulence factors encompass iron acquisition system (basD), phospholipase D (slpD), surface antigen protein A (surA), and penicillin-binding protein G (bpbG) [7,8]. Therefore, the present study aimed to identify nine diverse virulence genes in A. baumannii isolates isolated from patients with pneumonia hospitalized in the Intensive Care Unit (ICU) of Imam Khomeini Hospital, Tehran, Iran.…”
Section: Introductionmentioning
confidence: 99%